Divergent functions of the GAGA‐binding transcription factor family in rice. (5th March 2018) - Gong, Rong; Cao, Huasheng; Zhang, Jianing; Xie, Kun; Wang, Dianwen; Yu, Sibin
Summary: OsGBP s are a small family of four genes in rice ( Oryza sativa  L.) that function as transcription factors recognizing the GAGA motif; however, their functions in plant growth and development remain unclear. Here we report the functions of OsGBP s in plant growth and grain development. Knock‐down and knock‐out of OsGBP1 promoted seedling growth and enhanced grain length, whereas overexpression of OsGBP1 exhibited the opposite effect on seedling growth and grain length, indicating that OsGBP1 repressed grain length and seedling growth. In addition, overexpression of OsGBP1 led to delayed flowering time and suppressed plant height. OsGBP1 could regulate OsLFL1 expression through binding to the (GA)12 element of its promoter. In contrast, OsGBP3 induced grain length and plant height. Grain length and plant height were decreased in OsGBP3 RNAi lines and were increased in OsGBP3 overexpression lines. We also found a synergistic effect of these two genes on grain width and plant growth. RNAi of both OsGBP1 and OsGBP3 resulted in severe dwarfism, compared with RNAi of a single gene. These results suggest the presence of functional divergence of OsGBP s in the regulation of grain size and plant growth; these results enrich our understanding of the roles of GAGA‐binding transcription factors in the regulatory pathways of plant development. Significance Statement: The function of a small family of plant‐specific transcription factors that encode the GAGA‐binding proteins has not been defined in rice. Here, we report two types of OsGBPs are of independent origin, and play important roles in plant vegetative growth and reproductive development in rice. They have different functions in the modulation of plant height, flowering time and seed size.